Facilitators and barriers of patient-centered care at the organizational-level: a study of three district hospitals in the central region of Ghana - Abekah-Nkrumah, G.; Nkrumah, J. (BMC Health Services Research, 2019)
Background: Improving patient experience of care has gained enormous attention from policy makers and providers of healthcare services in Ghana. In spite of the supposed support for patient-centered care as the means for improving patient experience of care, scientific evidence point to poor patient experience of care in Ghana. Moreover, there seem to be little evidence on organizational-level factors that facilitate or hamper patient-centered care. In this study we assess organizational-level factors that facilitate or impede patient-centered care in three district hospitals in the Central Region of Ghana. Methods: The study was exploratory research that used qualitative methods to collect data from seven senior managers and 3 junior managers in three district hospitals in the Central Region of Ghana. Data were collected with the aid of an interview guide and a checklist. Data were analyzed using content analysis. Results: Two main Organizational-level factors were identified, namely, facilitators and barriers of patient-centered care. Facilitators to patient-centered care included: 1) Leadership commitment. 2) Leadership support. 3) Training and education for patient-centered care. Patient-centered care barriers identified in the hospitals were: 1) Leadership conceptualization of patient-centered care. 2) Lack of goals and sufficient activities for patient-centered care. 3) Communication related challenges.4) Ownership type. 5) Degree of centralization. 6) Financial constraints. Conclusion: Organizational-level factors that promoted patient-centered care were fairly present in the hospitals. Yet, several other factors negatively affected patient-centered care in the hospitals. A suitable patient-focused intervention is recommended for implementation at the health system and institutional-levels to improve patientcentered care. Hospitals managers should develop suitable goals and activities to stimulate patient-centered care with the full participation of hospital employees and patients and families.
Research Article
Keywords: Patient-centered care; Organizational-level factors; Patient-centered care facilitators; barriers